Palladium-Catalyzed Arylation of Ketones and Acetonitrile with Ortho Alkylation of Aryl Rings: De Novo Synthesis of Tetralines and Benzocycloheptenes - Lei, Chuanhu (2017)
Palladium-catalyzed α-arylation reactions of ketones with simultaneous ortho alkylation offer 1,2,3-substituted arenes. The reactions of 1,ω-dihaloalkanes also allow facile construction of medicinally important tetralines and benzocycloheptenes.